Pengaruh Brand Authenticity Terhadap Brand Attachment (Studi Kasus Pada Sepatu Olahraga Adidas) - Erwin Saputra (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Adidas is one of the most famous brands of sports shoes in the world after Nike. This can be seen from the sales data of Adidas’ sports shoes which were ranked second in 2017. Even though the sales of Adidas’ sports shoes increased compared to 2016, Adidas’ sales were still far below Nike’s. Adidas can utilize the brand authenticity that they have to increase their consumer’s brand attachment, so it can increase their sales. This study used a questionnaire method distributed to 192 respondents in Jabodetabek who had used Adidas’ sport shoes and then processed the data using SPSS. From this study it can be concluded that the brand authenticity significantly and positively influences the brand attachment of Adidas sports shoes users. In addition, it was also found that brand experience can positively moderate the influence of brand authenticity on brand attachment from Adidas sports shoes users.